ATRT-01. SYNCHRONOUS CENTRAL NERVOUS SYSTEM (CNS) ATYPICAL TERATOID/ RHABDOID TUMOR (AT/RT) AND MALIGNANT RHABDOID TUMOR OF THE KIDNEY - REVIEW OF THE LITERATURE - Abu Arja, Mohammad H (Neuro Oncol, 2018)
BACKGROUND: CNS AT/RTs with synchronous/ metachronous extra-CNS primary tumors are a rare entity with a dismal prognosis. METHODS: A literature review was conducted on patients diagnosed with CNS AT/RT and synchronous/ metachronous extra-CNS primary tumors. RESULTS: Our review yielded information on 32 children diagnosed with CNS AT/RT with additional extra-CNS primary tumors. The median age at diagnosis was four months. Male: female ratio was 2:1. Twenty-three patients presented within the age of six months. The most common extra-CNS site was the kidney (69%). Germline SMARCB1 mutation was found in all of the tested patients. The median overall survival was 5.8 months post-diagnosis. Only four patients were found to be alive with no evidence of relapse. All of the survivors receive high-dose chemotherapy (HDCT) followed by autologous peripheral blood stem cell transplant (PBSCT). Three of them had gross-total resection of the intracranial tumor and one did not receive any intracranial surgical resection. Two of the survivors did not receive any radiotherapy. One child received upfront focal radiotherapy, while the remaining patient received focal radiotherapy only after the progression of the intracranial tumor. Three of the surviving patients received intrathecal chemotherapy; two of them included methotrexate. CONCLUSION: The rarity of patients with CNS AT/RT with additional extra-CNS manifestations and the lack of a standard treatment protocol have contributed to the reported dismal prognosis. A multimodal treatment approach including maximal surgical resection, intrathecal chemotherapy, and HDCT with peripheral PBSCT may improve the outcomes for this patient population, without the need for upfront radiotherapy.